Locomotor deficits induced by lumbar muscle inflammation involve spinal microglia and are independent of KCC2 expression in a mouse model of complete spinal transection. - Jeffrey-Gauthier, Renaud (Exp Neurol, 2020)
Spinal cord injury (SCI) is associated with damage to musculoskeletal tissues of the spine. Recent findings show that pain and inflammatory processes caused by musculoskeletal injury mediate plastic changes in the spinal cord. These changes could impede the adaptive plastic changes responsible for functional recovery. The underlying mechanism remains unclear, but may involve the microglia-BDNF-KCC2 pathway, which is implicated in sensitization of dorsal horn neurons in neuropathic pain and in the regulation of spinal excitability by step-training. In the present study, we examined the effects of step-training and lumbar muscle inflammation induced by complete Freund’s adjuvant (CFA) on treadmill locomotion in a mouse model of complete spinal transection. The impact on locomotor recovery of each of these interventions alone or in combination were examined in addition to changes in microglia and KCC2 expression in the dorsal and ventral horns of the sublesional spinal cord. Results show that step length and angular motion at the hip, knee and ankle joint during locomotion were decreased by CFA injection and improved by step-training. Moreover, CFA injection enhanced the expression of the microglial marker Iba1 in both ventral and dorsal horns, with or without step-training. However, this change was not associated with a modulation of KCC2 expression, suggesting that locomotor deficits induced by inflammation are independent of KCC2 expression in the sublesional spinal cord. These results indicate that musculoskeletal injury hinders locomotor recovery after SCI and that microglia is involved in this effect.